2020
DOI: 10.1111/iju.14171
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silodosin and tadalafil on bladder dysfunction in spontaneously hypertensive rats: Possible role of bladder blood flow

Abstract: Objectives To investigate the effects of an alpha1‐adrenoceptor antagonist, silodosin, or a phosphodiesterase type 5 inhibitor, tadalafil, on bladder overactivity in spontaneously hypertensive rats. Methods Twelve‐week‐old male spontaneously hypertensive rats were perorally administered silodosin (100 µg/kg), tadalafil (2 or 10 mg/kg) or vehicle once daily for 6 weeks. Wistar rats were used as normotensive controls and were treated with the vehicle. At 18‐weeks‐old, the effects of silodosin or tadalafil on blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…24 Vascular factors, such as high blood pressure, have been also involved in the physiopathology of OAB. 25 The possible mechanism is due to higher sympathetic activity in patients with OAB, which in turn leads to an increase in blood pressure. 26 An alternative mechanism involves changes in bladder vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…24 Vascular factors, such as high blood pressure, have been also involved in the physiopathology of OAB. 25 The possible mechanism is due to higher sympathetic activity in patients with OAB, which in turn leads to an increase in blood pressure. 26 An alternative mechanism involves changes in bladder vascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have reported that silodosin improved BBF in not only a BOO rat model, but also an atherosclerosis rat model, in induced chronic bladder ischemia and a spontaneously hypertensive rat model. 8,9,[16][17][18] Additionally, Yonekubo et al reported that silodosin improved voiding efficiency by increasing BBF in a diabetic cystopathy-associated DU rat model. 19 Goi et al reported that silodosin prevented the decrease in nerve distribution of the bladder and the increase in nerve growth factor expression by improving BBF in an atherosclerosis rat model, and ameliorated detrusor contractile function.…”
Section: Discussionmentioning
confidence: 99%
“…First, the increase in the BBF induced by both silodosin and tadalafil might contribute to the improvement of bladder function. Several animal studies have reported that silodosin improved BBF in not only a BOO rat model, but also an atherosclerosis rat model, in induced chronic bladder ischemia and a spontaneously hypertensive rat model 8,9,16–18 . Additionally, Yonekubo et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations